2007
DOI: 10.1593/neo.06616
|View full text |Cite
|
Sign up to set email alerts
|

Target Therapy Using a Small Molecule Inhibitor against Angiogenic Receptors in Pancreatic Cancer

Abstract: These data highlight VEGF-RII and FGF-RI as therapeutic targets and suggest a potential role for the combined use of tyrosine kinase inhibitors in the management of inoperable pancreatic cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…28 The experimental protocol was approved by the Chancellor's Animal Research Committee of the University of Heidelberg (Heidelberg, Germany) in accordance with national guidelines for animal care and the use of laboratory animals. The poorly differentiated human pancreatic cancer cell line MIA-PaCa-2 was used for xenograft tumor induction.…”
Section: Evaluation Of Msc Differentiationmentioning
confidence: 99%
“…28 The experimental protocol was approved by the Chancellor's Animal Research Committee of the University of Heidelberg (Heidelberg, Germany) in accordance with national guidelines for animal care and the use of laboratory animals. The poorly differentiated human pancreatic cancer cell line MIA-PaCa-2 was used for xenograft tumor induction.…”
Section: Evaluation Of Msc Differentiationmentioning
confidence: 99%
“…By targeting both receptors, PD17304 should be both anti-angiogenic and anti-mitogenic, thereby potentially abrogating two critical pathways in tumor growth and metastasis [94]. Preclinical trials in orthotopic mouse models showed significant reduction in tumor growth, a lower incidence of metastatic spread, and a lower volume of ascites in PD173074-treated animals [95]. These data suggest that PD17304 may be a promising new treatment option for PDAC.…”
Section: Small-molecule Inhibitors Targeting Growth Factors And/or Thmentioning
confidence: 98%
“…The tumor size in the subcutaneous xenograft model was measured every 6 days using a vernier caliper, while in the two orthotopic xenograft models the size of the tumor was measured using an in vivo animal fluorescence imager (Carestream Health, Rochester, NY, USA) (excitation wavelength, 530 nm; emission wavelength, 600 nm). The average tumor volume (V) was calculated using the following equation: V = A x B 2 x 0.5 (A, long diameter; B, short diameter) (10). The tumor growth rate (U) was calculated using the equation U = V (mm 3 )/tumor-bearing time (days).…”
Section: Preparation Of Pancreatic Cells Stably Expressing Red Fluorementioning
confidence: 99%